Representations of Muslim Bodies in The Kingdom: Deconstructing Discourses in Hollywood - Michelle Aguayo (Global Media Journal: Canadian Edition, 2009)
In this post September 11 (9/11) climate of the “War on Terror”, Hollywood political-thriller films carry a new cultural currency. Drawing from literature in postcolonial studies and its engagement with representations in popular culture, this paper analyzes the film The Kingdom (2007)—a fictional political-thriller with a storyline inspired by real terrorist bombings in Saudi Arabia. This paper critiques and notes the film’s narrative practices, with particular attention paid to the racial and gendered discourses produced in it. In examining the representational codes and politics in the film’s construction of Muslim bodies post-9/11, it is argued here that a critical engagement with Hollywood cinema is necessary in order to reveal the complex ways in which Muslim bodies are scripted as dangerous, pre-modern and uncivilized in American popular culture. This analysis will expose how representations of Muslims in Hollywood not only are essentialized, but act simultaneously to discipline these bodies, which is grounded in the trope of the “War on Terror”, intimately linking it to the project of empire. A commitment to deconstructing Muslim bodies in Hollywood will illustrate the embeddedness of racialized and gendered imaginings of “Others” as they unfold not only “on-screen”, but also their relationship to violent colonial projects “off-screen”.